Impact of customer focus on technology leadership via technology development capability – a moderated mediation model. Issue 2 (18th May 2021) - Husain, Zafar; Dayan, Mumin; , Sushil; Di Benedetto, C. Anthony
Abstract : Purpose: This study aims to develop and empirically examine a model that investigates the mediating role of technology development capability (TDC) on the relationship between customer focus (CF) and technology leadership (TL). Design/methodology/approach: The analysis and interpretation of a partial least square model include the following two stages: the first stage focuses on assessing the reliability and validity of the measurement model, while the second pertains to evaluating the structural model. Findings: The general understanding prevailing in practice and literature is that management sponsorship (MS) has a positive impact on the relationship between CF and TDC. It is also generally understood that MS has a positive impact on TL initiatives. However, the findings of this study contradict these assumptions. Specifically, the study indicates that MS has a negative moderating effect on CF and technology development capabilities, and has no impact on CF and TL relationships. Originality/value: CF, TDC and MS, and their interplay and impact in enhancing firms' TL position, have not been explored thus far in an integrated manner in the context of the automobile industry in developing countries. The research relating to CF, technology development capabilities, technology innovation capabilities, MS and TL reported in the literature has drawn inferences from case studies, anecdotal evidence and experiences of industry leaders, experts and consultants. This study attempts to fill the gaps mentioned above by presenting and testing a new moderated mediation model that shows the relationship between CF, TDC, MS and TL.